Plantar Soft Tissue Multiscale Structure and Mechanics With Emphasis on Diabetes-Related Changes - Brady, Lynda M (ProQuest Dissertations & Theses, 2023)
Diabetes mellitus is a significant chronic disease affecting over 37 million Americans. Complications of the lower extremity related to diabetes can be severe, including deformity, ulceration, and amputation. Developing improved prevention and treatment of pedal complications necessitates a better fundamental understanding of the diabetes-related changes to plantar soft tissue microstructure and mechanics. Despite growing agreement that aberrant pressures are associated with ulceration, long-standing hypotheses about shear stresses initiating ulcer injury, and observational assessments of microstructural and biochemical disruptions, microstructural study has not assessed the characteristics of the unique adipose septal chambers of the plantar fat pad, and there has been little in vivo measurement of internal multidimensional strains. This gap in knowledge can be related to the difficulty of measuring these important parameters, as microstructural assessment requires substantial time from a highly trained histologist, and in vivo measurements must prioritize human safety and comfort. In order to address these lingering questions, this work develops physical and computational tools to make previously unexplored microstructural, macrostructural, and mechanical measurements of the plantar soft tissue.First, an automated method for assessing morphology of plantar soft tissue histological samples is reported and applied to quantify changes in the plantar adipose chambers related to tissue depth and diabetes. Adipose chambers were found to be quantitatively smaller in the superficial adipose layer than in the deep adipose layer, and with diabetes the size of the superficial chambers increased and the deep chambers decreased, leading to more similar chamber sizes between the two layers. Then, a volumetric load-bearing ultrasound scanner is constructed to acquire high-resolution, three-dimensional structural scans of the plantar soft tissues in unloaded and naturally loaded conditions. This scanner consists of an elevated platform, a two-axis mechanical translation system for the transducer, and a load-bearing plate capable of transmitting B-mode and shear wave elastography ultrasound modalities. In order to more safely couple the foot and transducer to the load bearing plate, custom polyacrylamide coupling gels were developed to meet application demands for strength and toughness. Finally, the volumetric scanner was integrated into a data collection protocol including computed tomography and plantar pressure, and scans were acquired for four subjects. Analytical methods for acquiring internal axial and shear strains across all three anatomical axes and planes, regional stiffness maps, and plantar pressure based on underlying bony geometry are reported. These methods are applied to the data from several subjects to demonstrate their feasibility.